2016
DOI: 10.4103/1596-3519.188891
|View full text |Cite
|
Sign up to set email alerts
|

Prestroke treatment of stroke risk factors: A cross-sectional survey in central Nigeria

Abstract: Background:Stroke can be prevented with treatments targeted at hypertension, diabetes mellitus, hyperlipidemia and atrial fibrillation, but this is often hampered by under-diagnosis and under-treatment of those risk factors. The magnitude of this problem is not well-studied in sub-Saharan Africa.Materials and Methods:We conducted a cross-sectional survey of stroke patients at a tertiary hospital during January 2010 to July 2013 to determine patient awareness of a pre-existing stroke risk factor and prior use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The prevalence of stroke in sub-Sahara Africa, as Alkali et al, (2016) observe, could be attributable to under-diagnosis and under-treatment of hypertension, hyperlipidemia and atrial fibrillation. Pre-hospital procrastination in accessing medical care for acute stroke usually, as Mellon et al, (2014) observe, attracts the unwanted.…”
Section: Growing Cases Of Stroke Among Young Adults In Nigeriamentioning
confidence: 90%
“…The prevalence of stroke in sub-Sahara Africa, as Alkali et al, (2016) observe, could be attributable to under-diagnosis and under-treatment of hypertension, hyperlipidemia and atrial fibrillation. Pre-hospital procrastination in accessing medical care for acute stroke usually, as Mellon et al, (2014) observe, attracts the unwanted.…”
Section: Growing Cases Of Stroke Among Young Adults In Nigeriamentioning
confidence: 90%
“…Initially, 27 individuals with suspected cardioembolic stroke exhibited unremarkable findings on ECGs. Subsequent evaluation was conducted through 24-hour Holter monitoring, revealing the presence of AF [40]. The SIREN (Stroke Investigative Research and Educational Network) study, initiated in August 2014 as a multicenter case-control investigation across diverse sites in Nigeria and Ghana, provided valuable insights into the association between AF and stroke.…”
Section: Af and Strokementioning
confidence: 99%
“…5,6 The public also lacks adequate knowledge of stroke risk factors such as hypertension, diabetes mellitus, obesity, high cholesterol, physical inactivity and cigarette smoking that are potentially reversible with medical treatment and changes in lifestyle. [7][8][9] In a study from Thailand, a third of stroke survivors didn't know a single stroke risk factor, while a Nigerian study found two- thirds of patients with raised cholesterol only knew of their high risks after they experienced stroke. 7,9 In another study from Nigeria and Ghana, hypertension was the only risk factor identified by a majority of stroke survivors, their family members and healthcare staff, most of whom lacked knowledge of stroke risks due to diabetes, obesity, high cholesterol and cigarette smoking.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In a study from Thailand, a third of stroke survivors didn't know a single stroke risk factor, while a Nigerian study found two- thirds of patients with raised cholesterol only knew of their high risks after they experienced stroke. 7,9 In another study from Nigeria and Ghana, hypertension was the only risk factor identified by a majority of stroke survivors, their family members and healthcare staff, most of whom lacked knowledge of stroke risks due to diabetes, obesity, high cholesterol and cigarette smoking. 10 Other studies similarly reported poor knowledge of stroke among Nigerians, although a few studies found good knowledge.…”
Section: Introductionmentioning
confidence: 99%